2010
DOI: 10.1074/jbc.m109.094722
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Cell Division Inhibitor PC190723 Is an FtsZ Polymer-stabilizing Agent That Induces Filament Assembly and Condensation

Abstract: It is yet to be investigated whether both ligands target structurally related assembly switches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
196
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(216 citation statements)
references
References 51 publications
(61 reference statements)
18
196
2
Order By: Relevance
“…Both sets of mutants (Mj-group E and Sa-resistant), although not completely coincident, delineate the long cleft between the C-domain and H7, which is in a position equivalent to the taxol binding site of tubulin. PC190723 is a polymer-stabilizing agent for Bs-FtsZ and Sa-FtsZ (9). It is to be investigated whether this compound, by binding to said cleft, interferes with the curved-straight switching in Bs-FtsZ and Sa-FtsZ, similarly to what taxanes do for tubulin by favoring its assembled straight form (65,66).…”
Section: Ftsz Monomer Flexibility and Predicted Subdomain Movements Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sets of mutants (Mj-group E and Sa-resistant), although not completely coincident, delineate the long cleft between the C-domain and H7, which is in a position equivalent to the taxol binding site of tubulin. PC190723 is a polymer-stabilizing agent for Bs-FtsZ and Sa-FtsZ (9). It is to be investigated whether this compound, by binding to said cleft, interferes with the curved-straight switching in Bs-FtsZ and Sa-FtsZ, similarly to what taxanes do for tubulin by favoring its assembled straight form (65,66).…”
Section: Ftsz Monomer Flexibility and Predicted Subdomain Movements Mmentioning
confidence: 99%
“…GTP analogs substituted at C8 selectively inhibit purified FtsZ while supporting tubulin assembly (7). FtsZ has been validated as the target of an effective bactericidal compound PC190723 (8), which is an FtsZ polymer-stabilizing agent (9).…”
mentioning
confidence: 99%
“…Nevertheless, thiostrepton for IF-2, pulvomycin and GE2270A for EF-Tu, and PC190723, Berberine and Zantrins for FtsZ have been exploited and investigated for their inhibitory activity towards those GTPases. [29][30][31][32][33][34][35][36][37][38] The recent technological advances in computational modeling of protein structures have a crucial role in drug design and its retrieval. In our study, structure-based pharmacophore design screened a relatively small number of candidate molecules and we successfully identified three inhibitors (SBI-34462, -34566, and -34612) for an essential bacterial GTPase Der that has been unexploited for antibacterial target.…”
Section: Models Of Der Gtpase Complexes With Bioactive Compoundsmentioning
confidence: 99%
“…Andreu and coworkers found that PC190723 inhibited GTPase activity of B. subtilis FtsZ through inducing FtsZ polymers into straight bundles and ribbons. The result suggested that PC190723 inhibit FtsZ via the stabilization of the FtsZ polymerization [92]. Lumb and co-workers also conducted some structural and biochemical analyses of S. aureus FtsZ with PC190723.…”
Section: Dichamanetin and Its Derivativementioning
confidence: 99%